Oral mycotic infection caused by a rare Verticillium species - a case report - Saqib Habib; Nighat Naved; Muhammad Sohail Awan (BMC, 2023)
Abstract Background Deep-seated fungal infections of the oral cavity present a diagnostic challenge as the clinical presentation is usually aggressive leading to misdiagnosis of malignancy. Nevertheless, the species of fungi responsible for such diseases in immunocompromised individuals are varied thus, further complicating the diagnosis. Case presentation Presented below is a case regarding the diagnosis and management of deep mycotic infection of the oral cavity caused by a fungus that very rarely causes disease in humans, the Verticillium species. Conclusions The case highlights the fact that rare pathogens should also be considered in the differential diagnosis, especially in patients with debilitating conditions like uncontrolled diabetes. Likewise, histopathological evaluation and microbiological investigations are of paramount importance and remain the gold standard to reach a definitive diagnosis.